Women at the Helm: Navigating the Digital Landscape of Agriculture - Dominic, D.M.; Bhuvana, N.; Mittal, N.; Sulaiman, R.V.; Puskur, Ranjitha (International Rice Research Institute, 2024)
Agribusiness startups are reshaping India’s agricultural sector, fostering a strong entrepreneurial mindset. This growing interest, alongside advancements in digital technology, has spurred rapid expansion in the sector’s technology and digital solutions ecosystem. Technologies like big data, Artificial Intelligence (AI), Internet of Things (IoT), and various digital platforms play a crucial role, aiding aspiring entrepreneurs from idea conceptualization to identifying opportunities in production, marketing, and distribution. The proliferation of digital technologies presents unprecedented opportunities for women to engage and lead agricultural enterprises in India, overcoming longstanding barriers such as limited access to information, resources, and markets. Despite these advancements, challenges persist, and adoption of digital technologies varies widely among enterprises. In the Indian context, research on the use of digital solutions by women agripreneurs remains limited. In 2023, the Centre for Research on Innovation and Science Policy (CRISP) and the International Rice Research Institute (IRRI) conducted a study, as part of the Evidence Module of the CGIAR GENDER Impact Platform, interviewing 16 selected women agripreneurs in India. The study aimed to understand their utilization of digital tools, exploring the types of tools used, developed digital solutions, and how these facilitate enterprise-building processes. Each entrepreneur shared insights on their use of digital tools, highlighting benefits in networking, self-learning, upskilling, education, e-commerce, sales, and enterprise management. While digital technologies have opened avenues for career advancement, women agripreneurs acknowledge gaps in fully harnessing these potentials. The study identified two types of enterprises led by women in the digital ecosystem: digitech enterprises, often founded by women with a background in technology, and digitally enabled enterprises, leveraging various digital technologies to promote their businesses. The majority of women entrepreneurs operate digitally enabled enterprises, reflecting the tech-driven nature of modern agribusiness. This compilation of interviews illustrates how digital innovations support women agripreneurs in India, showcasing their entrepreneurial journeys, aspirations, challenges, and strategies to overcome these challenges through digital interventions and other forms of support. It is intended to benefit those supporting women agripreneurs, particularly within India’s agribusiness incubation centres, offering valuable insights and lessons for leveraging digital innovations to enhance enterprise performance. We sincerely believe that each of these life stories will also inspire several budding women agripreneurs and help them assess their digital capacity gaps and take steps to address these.